Biofuel imaginaries: The emerging politics surrounding 'inclusive' private sector development in Madagascar. (June 2016) - Neimark, Benjamin D.
Abstract: Biofuels are just one of a host of bioeconomy initiatives which promise to deliver 'inclusive' sustainable development through innovations in bio-based products and services in the global south. Yet to critics, biofuels are seen as prime drivers in a global 'land grab, ' rainforest clearance, and the dispossession of farmers. Responding to these concerns, firms in Madagascar have shifted production away from large plantations to small-scale production of the more 'environmentally-friendly' biofuel crop Jatropha curcas . Using a political ecology lens and building upon critical discourse analysis found in cultural political economy, I analyse perspectives of on the material effects and emerging politics surrounding a case of a British-biofuel start-up firm in the northwest Madagascar. I demonstrate that access to biofuel land and labour is dependent upon the inclusion of Malagasy in rural development projects. However, rather than delivering on the promises of biofuels, jatropha has largely emerged as a failed development strategy. This article examines the unaccounted for power that varied and diverse actors derive by promoting the inclusion of individuals and groups to share in benefits, and the material consequences of private sector development in the global south. Highlights: Critical integration of political ecology and cultural political economy. Illustrates the discursive construction of 'the bio-economy'. Exposes the material consequences of private sector led rural development. Examines the effects of biofuel promotion as sustainable and inclusive.